ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT. KALBE FARMA TBK TAHUN (2016-2020) - Muhammad Azizil Taufiq; Nurman; Hety Budianti (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine how the financial performance of PT. Kalbe Farma, Tbk in 2016 to 2020 and to find out whether or not there is a difference between the EVA value produced by the company before the 2016-2019 pandemic and during the 2020 pandemic. The population in this study is the company's annual financial report, while The sample used is the company's balance sheet and income statement. The data collection technique in this study is user documentation, then it will be analyzed using the Economic Value Added (EVA) method, which consists of the calculation of NOPAT, Invested Capital, WACC, Capital Charge, and EVA which is then tested using the Kruskal Wallis H Test method. The results of this study indicate that the company's EVA value from 2016 to 2020 continues to be positive, so it can be said that there is an economic added value to the company. Then, based on the Kruskal Wallis H Test by producing the Asymp value. Sig. of 0.157 (p > 0.05), it can be said that there is no difference in the EVA value generated by the company in the period before the 2016-2019 pandemic with the period during the 2020 pandemic.